La evolución del sector construcción y el empleo en el departamento de Loreto periodo 2016 - 2020 - Rodríguez Luna, Marco Antonio (2023)
Almost always, a growth in the Construction sector brings with it an increase in employment, mainly due to the demand for unskilled labor. The current doctoral thesis aims to determine the relationship between the evolution of the Construction sector and Employment in the department of Loreto in the period 2016 - 2020. Because of this, this research is carried out classified as Quantitative, Correlational and design level. Not experimental. The analysis of the results obtained concludes that there is no direct relationship between the evolution of the Construction sector and Employment in the department of Loreto during the period 2016 - 2020, verified by means of the statistical test, where the Correlation Coefficient reached r = 0.718884615; and the Determination Coefficient that was R2 = 0.516795090; values far from the minimum required for a good statistical association. The Construction sector is not considered among the three most important in the generation of the regional product, ranking rather in eighth place with S/. 1,415.86 million, equivalent to 3.47% of the total value. The first place corresponds to Commerce with S/. 7,341.36 million (17.48%). For its part, employment had a variable behavior, but it grew moderately at an average annual rate of 0.21%, which represents an employed population of 506.86 thousand people. The average monthly income from work maintained a growing trend.